Health Related Quality of Life of Hypertensive Patients attending a Tertiary Level Hospital in Kathmandu - Chhetri, R.; Bista, B.; Pandeya, P.; Khanal, S.P.; Neupane, A. (Journal of Manmohan Memorial Institute of Health Sciences, 2023)
Background: Hypertension among cardiovascular disease is one of the major components of non-communicable disease emerging as a global public health problem leading the risk for disability and death globally impairing health related quality of life (HRQoL). The objective of study was to find out the health related quality of life of hypertensive clients attending a tertiary level hospital. Methods: A cross-sectional study was conducted at Manmohan Cardiothoracic Vascular and Transplant Center among 153 hypertensive clients attending outpatient department. Simple random sampling technique was used to collect data. Face to face interview was done for data collection, using structured questionnaire that included socio-demographic variables, health related variables, lifestyle related variables and RAND Short Form (SF)-36 questionnaire. Data analysis was done by using descriptive statistics and inferential statistics. Results: More than half of respondents (61.4%) had good level of health related quality of life in physical component score while 86.3% had good level of health related quality of life in mental component score. The level of HRQoL was significantly associated with health related variables such as comorbidities, diabetes, cardiovascular diseases and lifestyle related variables such as sleeping pattern, type of exercise in physical component and sleeping pattern in the mental component. Conclusion: The level of HRQoL of hypertensive clients is found to be good. Hypertensive clients could improve HRQoL through prevention and treatment of diabetes and cardiovascular diseases.